Research on salt tolerance of OsProDH -mutant Bac Thom 7 rice variety - Phuong, Nguyen Duy; Huyen Ngoc, Ma; Le Quyen, Cao (Academia Journal of Biology, 2025)
Salt stress severely impacts rice productivity worldwide, with increasing soil salinization threatening food security in many regions. This study examined the physiological function of proline dehydrogenase (OsProDH) in salt stress responses using a Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9 (CRISPR/Cas9)-edited Bac Thom 7 (BT7) rice line carrying a 39-nucleotide deletion in the OsProDH gene. Seedlings of wild-type and mutant plants were subjected to 100−200 mM NaCl treatments to evaluate biochemical and physiological responses. Free proline quantification revealed distinct accumulation patterns, with the OsProDH mutant maintaining significantly higher proline levels before stress (1.8-fold) and during recovery (1.6-fold). Oxidative stress markers showed that the mutation significantly reduced salt-induced reactive oxygen species (ROS) accumulation, with H2O2 content decreased by 41% and malondialdehyde (MDA) levels reduced by 37% compared to wild-type plants under 100 mM NaCl. Antioxidant enzyme analysis revealed a selective enhancement pattern in the mutant, with peroxidase (POD) and ascorbate peroxidase (APX) activities increased by 42% and 38% respectively, during salt stress. Under severe salt stress (200 mM NaCl), physiological parameters, including survival rate and chlorophyll content, showed only minor improvements in the mutant despite substantial biochemical protection. These results demonstrate that OsProDH influences BT7 rice salt responses through multiple pathways, particularly in the regulation of proline metabolism and specific antioxidant enzyme activities. The findings contribute to our understanding of proline metabolism in cereal crops and provide insights for future development of salt-resilient rice varieties.